2010
DOI: 10.1128/aem.01693-09
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Hop Inhibition Include the Transmembrane Redox Reaction

Abstract: In this work, a novel mechanistic model of hop inhibition beyond the proton ionophore action toward (beer spoiling) bacteria was developed. Investigations were performed with model systems using cyclic voltammetry for the determination of redox processes/conditions in connection with growth challenges with hop-sensitive and -resistant Lactobacillus brevis strains in the presence of oxidants. Cyclic voltammetry identified a transmembrane redox reaction of hop compounds at low pH (common in beer) and in the pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 42 publications
(83 reference statements)
1
35
0
Order By: Relevance
“…This impairs enzymatic activity and nutrient transport, halting growth and ultimately killing the cell (220,221). In addition, iso-alpha-acids participate in transmembrane redox reactions in association with manganese, causing oxidative stress to the bacterial cell (222), which explains the manganese-dependent enhancement of transmembrane potential observed previously (219,221) (Fig. 4).…”
Section: Pediococcus Damnosus Pediococcus Inopinatus Pediococcus Dementioning
confidence: 83%
See 1 more Smart Citation
“…This impairs enzymatic activity and nutrient transport, halting growth and ultimately killing the cell (220,221). In addition, iso-alpha-acids participate in transmembrane redox reactions in association with manganese, causing oxidative stress to the bacterial cell (222), which explains the manganese-dependent enhancement of transmembrane potential observed previously (219,221) (Fig. 4).…”
Section: Pediococcus Damnosus Pediococcus Inopinatus Pediococcus Dementioning
confidence: 83%
“…Hop stress in L. brevis also induces expression of a broad range of proteins involved in redox homeostasis, DNA repair, and protein repair, facilitating a shift toward energy balance and metabolic regulation to cope with low-pH conditions and oxidative stress (225). The multiple modes of inhibition exerted by hop challenge and the complex response elicited in resistant bacteria indicate that hop-resistant LAB are specialized for growth in beer through resistance to oxidative and acid stress (219,222). Early work demonstrated that iso-alpha-acids have no impact on the growth of Gram-negative bacteria (226), but no further work has been done to determine the mechanism for resistance.…”
Section: Pediococcus Damnosus Pediococcus Inopinatus Pediococcus Dementioning
confidence: 99%
“…Thus, the lag between stimulus and response yields a timeframe conducive to antimicrobial activity. Recently, the antibacterial action of hop compounds was suggested to involve potent redox reactivity, resulting in cellular oxidative damage (Behr and Vogel, 2010). Accordingly, in the absence of active phenotypic adaptation, the VPNC cells of beer-spoilage L. acetotolerans are probably sensitive and not equipped to detoxify superoxide and a proportion or all of these cells remain non-culturable.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for this phenomenon is that the cells respond to Mn 2+ limitation by upregulating these enzymes, thus compensating for the reduced levels of intracellular manganese and the lost activities of Mn 2+ -dependent enzymes 18 . Very recently, the antibacterial mechanisms of hop compounds were suggested to involve proton ionophoric actions and redox-reactive uncoupler activities occurring in parallel 19,162 . Accordingly, it is plausible that beer spoilage LAB have to cope with oxidative stress induced by hop compounds, in addition to PMF depletion.…”
Section: Part 2: Hop Resistance In Beer Spoilage Labmentioning
confidence: 99%
“…Accordingly, it is plausible that beer spoilage LAB have to cope with oxidative stress induced by hop compounds, in addition to PMF depletion. Thus, the observed upregulation of Mn 2+ -dependent enzymes responsible for redox homeostasis is most likely part of a defensive response to the oxidative stress caused by hop bitter acids 19,162 . On the other hand, a morphological shift into smaller rods was observed in beer-adapted L. brevis and L. lindneri cells (Fig.…”
Section: Part 2: Hop Resistance In Beer Spoilage Labmentioning
confidence: 99%